Towards decentralized IoT security enhancement: A blockchain approach. (November 2018) - Qian, Yongfeng; Jiang, Yingying; Chen, Jing; Zhang, Yu; Song, Jeungeun; Zhou, Ming; Pustišek, Matevž
Abstract: With the rapid development of internet of things (IoT), it has brought great convenience to users in different fields, such as smart home, smart transportation and so on. However, it also carries potential security risks. In order to solve this challenge, in this paper, we first introduce three layers of IoT, i.e., perception layer, network layer and application layer, then corresponding security problems of three layers are introduced. Second, we propose a high-level security management scheme based on blockchain for different IoT devices in the full life cycle. Finally, we give open research problems and future work.